2010
DOI: 10.1002/app.31764
|View full text |Cite
|
Sign up to set email alerts
|

Graphite carbon foam films prepared from porous polyimide with in situ formed catalytic nickel particles

Abstract: This article describes the preparation of porous polyimide composites and carbon foam films with uniform and controllable porous structures, using nickel oleate as a pore-forming agent and as a precursor for catalyst formation for the carbonization process. Pore formation occurs by a phase separation initially producing a dispersion of nickel oleate liquid in the polyamide acid film. Subsequent heat treatment induces decomposition of the nickel oleate accompanied by the evolution of foam forming gas. Small nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The XRD pattern of the as-obtained carbonized PAN fiber is shown in Figure 2. The broad peaks centered at around 26.2 ∘ and 43.7 ∘ are attributed to the (002) and (010) planes of the graphite carbon structure (JCPDS 41-1487) [19]. The fact that 002 diffraction peaks are relatively low in intensity and broad in shape suggests that as-prepared carbon nanofibers possess low graphitization and crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD pattern of the as-obtained carbonized PAN fiber is shown in Figure 2. The broad peaks centered at around 26.2 ∘ and 43.7 ∘ are attributed to the (002) and (010) planes of the graphite carbon structure (JCPDS 41-1487) [19]. The fact that 002 diffraction peaks are relatively low in intensity and broad in shape suggests that as-prepared carbon nanofibers possess low graphitization and crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have already noted that the graphitization process of carbon could be accelerated in the presence of some additives . Noda et al studied the graphitization process of coke with calcium hydroxide as a catalyst, and they found the graphitization of coke started at a temperature as low as 800°C with the coexistence of calcium hydroxide .…”
Section: Introductionmentioning
confidence: 99%
“…This result was amazing because the coke graphitize only above 2500°C without additive under atmospheric pressure. Matsuo and Fuertes indicated that Ni was a very effective catalyst to convert carbon into graphite at low temperature . However, the residual additives are usually harmful for the further application of graphite …”
Section: Introductionmentioning
confidence: 99%
“…As indicated from the XRD results (Fig. 5e), the Ni@PMMA-450/600 catalyst existed mainly in the form of NiO, metallic Ni, and Ni 3 C. Most of the carbon atoms formed an epitaxial graphite monolayer on the (111) plane of the Ni crystallites and finally precipitated in the form of graphitic carbon (OLC) at an appropriate temperature (600–850 °C), 70,71 and some combined with Ni to generate Ni 3 C, while NiO was further oxidized to Ni 2 O 3 . As the temperature increased, the peaks attributed to Ni 3 C and Ni 2 O 3 gradually disappeared, and the diffraction peak of metallic Ni became more intense and narrow.…”
Section: Resultsmentioning
confidence: 95%